Evaluasi Dana APBN Program Sanitasi Perdesaan 2023 terhadap Tingkat Stunting di Manutapen Kupang - Windy Tamara; Fransina W. Ballo; Aldarine Molidya (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The aim of this research is to assess and measure the source of APBN funding for the 2023 Labor-Intensive Rural Sanitation Program implemented by the government on the level of stunting in Manutapen Subdistrict, Alak District, Kupang City. This research uses a qualitative descriptive approach. Data collection used was interviews, observation and documentation. The results of the research show that APBN funding for the labor-intensive rural sanitation program in Manutapen Subdistrict, Alak District, Kupang City for the year 2023 for stunting prevention in Kupang City is still low, namely with a value of 1.23 compared to the threat which is quite high with a value of 1.6, so it will not get a significant value. Eradicating poverty and healthy lifestyles is one way to overcome stunting so that people can get a decent life by fulfilling economic needs according to standards.